ISOLATION AND PURIFICATION OF PREGNANCY-ASSOCIATED GLYCOPROTEINS - Yerzhanova, N.; Iskakova, I.; Zauatbayeva , G.; Keyer , V.; Sarina , N. (Eurasian Journal of Applied Biotechnology, 2022)
The aim of these studies was to develop a protocol for the isolation and purification of pregnancy-associated glycoproteins (PAG) from cotyledons from placenta of pregnant cows. As a result of this work, processes and parameters of the PAG isolation were determined, including: extraction in a buffer system, two-stage precipitation with ammonium sulfate (40% and 80% saturation) and purification of the target product using ion-exchange chromatography using Q Sepharose Fast Flow. The resulting product having a molecular weight of 55 kD was identified by MALDI-TOF mass-spectrometry analysis as "Pregnancy-associated glycoprotein 1". As a result of the immunoblotting, the presence of proteins with a molecular weight of 55 kDa in the obtained preparation, reacting with previously obtained monoclonal antibodies (MABs) specific to PAG1 was confirmed. To determine antigenic properties of the purified PAG, laboratory animals were immunized. It was found that immunization with the purified PAG efficiently elicits specific antibodies. These antibodies, after the proper purification procedure, can be used as components of immunological test systems for determining pregnancy in cows.